Skin Microbiota Content in Children and its Effect on Acne Pathogenesis - Larisa S. Kruglova; Natalia V. Gryazeva; Anait V. Tamrazova (Вопросы современной педиатрии, 2021)
Acne is a common chronic inflammatory skin disease in adolescence. The involvement of cosmetically important zones inevitably leads to decrease in our patients' quality of life. This review considers modern methods of skin microbiota analysis, describes the microorganisms' composition in newborns and its changes during growing-up. Cutibacterium acnes (that dominates in the microbiota of skin areas with sebaceous glands) role in acne pathogenesis is described.